2014
DOI: 10.1093/brain/awu257
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun activation in Schwann cells protects against loss of sensory axons in inherited neuropathy

Abstract: Charcot-Marie-Tooth disease type 1A is the most frequent inherited peripheral neuropathy. It is generally due to heterozygous inheritance of a partial chromosomal duplication resulting in over-expression of PMP22. A key feature of Charcot-Marie-Tooth disease type 1A is secondary death of axons. Prevention of axonal loss is therefore an important target of clinical intervention. We have previously identified a signalling mechanism that promotes axon survival and prevents neuron death in mechanically injured per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 41 publications
2
61
0
1
Order By: Relevance
“…3,63,64 In normal nerve, both genes are normally expressed in nonmyelinating SCs, but both L1CAM and NGFR are expressed in myelinating SCs of human skin. 66 Using the CMTES-R score, we did not observe a correlation of PMP22 mRNA levels (or NGFR/L1CAM) with severity of neuropathy. It is notable that most of the SC injury genes were not elevated in CMT1A.…”
Section: Discussionmentioning
confidence: 57%
“…3,63,64 In normal nerve, both genes are normally expressed in nonmyelinating SCs, but both L1CAM and NGFR are expressed in myelinating SCs of human skin. 66 Using the CMTES-R score, we did not observe a correlation of PMP22 mRNA levels (or NGFR/L1CAM) with severity of neuropathy. It is notable that most of the SC injury genes were not elevated in CMT1A.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, the CMT1A phenotype has previously been thought to recapitulate certain aspects of nerve injury, in which Schwann cells are reprogrammed to undergo demyelination and initiate a program involving macrophage recruitment, downregulation of myelin genes, and secretion of factors that ultimately support nerve regeneration. One of the critical regulators of Schwann cell responses to nerve injury is the c-Jun transcription factor (41), which is also induced at the protein level in both rodent models of CMT1A and also in Schwann cells of skin biopsies from human patients (40,42,43). While c-Jun was induced in C22 mice, the data obtained here allowed us to determine whether the broader profile of deregulated genes in C22 overlap with those found in nerve injury.…”
Section: Resultsmentioning
confidence: 80%
“…The present study focused on the controlled expression of the c-Jun gene to provide time-restricted neurotrophic support for nerve regeneration, whereas previous studies have also showed that c-Jun is associated with tumor formation in some systems (56), potentially suppresses myelin genes (57), and has been implicated in demyelinating neuropathies (58). It was reported that more than 1000 genes were regulated by c-Jun in SCs after nerve injury, including the up-regulation of GDNF, sonic hedgehog, oligodendrocyte transcription factor 1, inhibitor of DNA binding 2, SRY-box 2, and runt-related transcription factor 2 and the down-regulation of myelin protein zero, myelin basic protein, and peripheral myelin protein 22 (48,59).…”
Section: Discussionmentioning
confidence: 99%